Polymorphisms and AR: A Systematic Review and Meta-Analyses - Xiang, Feng; Zeng, Zhen; Wang, Lu; Yang, Ye Peng; Zhang, Qin Xiu (Frontiers in Genetics, 2022)
Background: Allergic rhinitis (AR) is an especially common disorder associated with both environmental and genetic factors, and a lot of researchers have attempted to find polymorphisms which predisposed to the disease. We conducted a meta-analysis of the most frequently researched polymorphisms to find those genes which may be susceptible to AR and then may be of value in diagnosis. Methods: Pubmed and China National Knowledge Infrastructure (CNKI) databases were searched to screen out eligible studies focusing on the correlation between polymorphisms and AR susceptibility, and then polymorphisms cited in at least 3 studies were selected. Results: The 142 papers originally selected cited 78 genes. Twelve genes (coinciding with 23 polymorphisms) were reported in more than three papers. Twenty-three polymorphisms were involved in the meta-analysis. Among the 23 polymorphisms, only 4 were found to be related to the risk of AR: IL-13 rs20541, CTLA-4 rs11571302, IL-4R RS1801275 and ACE (I/D). The remaining 19 of the 23 polymorphisms were not associated with AR. Conclusion: We found polymorphisms that could be used for AR diagnosing and those that were unrelated to AR. This may be the first step in detecting polymorphic combinations susceptible to AR (IL-13 RS20541, CTLA-4 RS11571302, IL-4R RS1801275 and ACE (I/D). In addition, our results may improve AR diagnosis and contribute to the intensive study of AR.